QuEChERS technique followed by GC-MS for trace detection of pesticides in vegetables and fruits - Huỳnh, Thị Túy Ngọc; Châu, Nguyễn Đăng Giáng (Hue University Journal of Science: Natural Science, 2023)
Pesticide residues in agricultural products are an essential measure to assess food safety. In this study, we successfully developed and validated an effective analytical method for the simultaneous determination of nine new-generation pesticides in vegetables and fruits. We employed the QuEChERS sample preparation technique, using MgSO4 and sodium acetate trihydrate for the initial clean-up step, followed by dispersive solid-phase extraction with PSA and GCB adsorbents, to remove all impurities in the sample matrix. GC-MS was then utilized for qualitative and quantitative analysis. The method exhibited a low detection limit for analytes (3–8 µg·kg–1), a 70–120% recovery, good repeatability, and good linearity. We applied the technique in practice to analyze 16 vegetable and fruit samples collected at markets in Thua Thien Hue province and found that the residues of some pesticides were at high levels.